2004
DOI: 10.1111/j.1365-2516.2004.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Cases of surgery in high‐responder haemophilia patients

Abstract: We present 11 cases of surgery in haemophilia patients with inhibitors (high responders). They were: one haemorroidectomy, one vesical surgery in a high responder, one adenoidectomy, seven orthopaedic procedures (one bone fixation of a femoral neck fracture, four total knee arthroplasties, two total knee arthroplasties), and one retroperitoneal haematoma that required emergency surgery. We conclude that surgery in haemophilia patients with inhibitor can be considered feasible but nevertheless remains difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 2 publications
0
31
0
1
Order By: Relevance
“…The cases covered by Tagariello in 2000 were considered in Goudemand et al Work published in 1996 by Ingerslev et al has been followed up and expanded in 2002 . Rodriguez‐Merchan et al have sequentially expanded upon their experience with publications in 2003, 2007 and 2010 …”
Section: Methodsmentioning
confidence: 99%
“…The cases covered by Tagariello in 2000 were considered in Goudemand et al Work published in 1996 by Ingerslev et al has been followed up and expanded in 2002 . Rodriguez‐Merchan et al have sequentially expanded upon their experience with publications in 2003, 2007 and 2010 …”
Section: Methodsmentioning
confidence: 99%
“…However, the majority of data on the use of rFVIIa are derived from case studies. A number of case studies have reported on the successful use of rFVIIa as haemostatic cover during elective surgery in haemophilia patients with high‐titer inhibitors [7,8,10–58]. In addition, results from a recent cost–benefit analysis suggest that major knee surgery using rFVIIa in haemophilia patients with inhibitors may be cost‐effective because of the reduced number of bleedings or improved quality of life experienced by these individuals following surgery [59].…”
Section: Introductionmentioning
confidence: 99%
“…Topical application of fibrin sealant during the intraoperative period to minimize capillary ooze and the use of vasoconstrictors and antifibrinolytics can be used to enhance the effect of rVIIa and improve haemostasis (Schulman 1998). Activated prothrombin complex concentrate (aPCC) has also been used to cover surgical procedures in haemophilia patients with inhibitors (Dimichele 2006;Goudemand 2004;Hvid 2002;Negrier 1997;Tjonnfjord 2004) and data suggests similar efficacy to rVIIa, albeit having the risk of an anamnestic rise in antibody titre (Schulman 1998), a risk not present with rVIIa. Current guidelines give equal merit to rVIIa and aPCC in managing bleeding in haemophilia (Hay 2006).…”
Section: Recombinant Factor Viiamentioning
confidence: 99%